2019
DOI: 10.3390/ijerph16010101
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lighting Problems on Eye Symptoms among Cleanroom Microscope Workers

Abstract: The visual health of microscope workers is an important occupational health concern, and a previous study suggested an association between lighting problems (e.g., flashing light, insufficient lighting) and eye symptoms among cleanroom workers in the electronics industry. This study aimed to explore the association between eye symptoms and lighting problems, as well as light-related counteracting behaviors among microscope workers in the cleanroom environment. Ninety-one cleanroom workers aged 20 years or olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
9
0
5
Order By: Relevance
“…The MN assay has historically been scored using manual slide microscopy, which benefits from high-resolution imaging of nuclear and cytoplasmic cellular components, but is prone to scorer fatigue and variability 15 . In addition, prolonged use of a microscope can lead to repetitive stress injuries, including back, neck, and vision problems 16 18 . To address these difficulties, automated methods have been developed, including slide-scanning microscopy and flow cytometry.…”
Section: Introductionmentioning
confidence: 99%
“…The MN assay has historically been scored using manual slide microscopy, which benefits from high-resolution imaging of nuclear and cytoplasmic cellular components, but is prone to scorer fatigue and variability 15 . In addition, prolonged use of a microscope can lead to repetitive stress injuries, including back, neck, and vision problems 16 18 . To address these difficulties, automated methods have been developed, including slide-scanning microscopy and flow cytometry.…”
Section: Introductionmentioning
confidence: 99%
“…The use of Display Screen Equipment (DSE) is associated with eye fatigue but evidence to date suggests it does not impact visual acuity (Larese Filon et al, 2019). Dry eye and eye fatigue are experienced by microscope workers in clean room facilities (Lin et al, 2019). Uveitis is not generally associated with occupational hazards other than traumatic eye injury, although since the aetiology of this condition is not fully understood, occupational factors cannot be ruled out (Choi et al, 2019).…”
Section: Ocular Problemsmentioning
confidence: 99%
“…Although there were no reported studies of ocular surface diseases conducted on garment factory workers, studies have reported DED in other occupational environments, such as cleanrooms [22,23] and in a chemical factory [24]. In a study investigating 91 cleanroom workers exposed to insufficient or flashing lights, 41.8% of the participants had symptoms of DED and 63.7% had symptoms of eye fatigue [22]. In another three-year study involving cleanroom workers, the TBUT and McMonnies questionnaire results worsened with more years of employment [23].…”
Section: Previous Studiesmentioning
confidence: 99%
“…As DED is affected by socioeconomics, lifestyle, occupations, and environmental factors, it is likely to have different associated factors in developing countries, such as Bangladesh, compared to developed countries. For instance, there may be more DED in cases of trachoma and vitamin A deficiency, and in special occupational groups [22][23][24].…”
Section: Introductionmentioning
confidence: 99%